Origanum majorana essential oil improves the rat’s sexual behavior and testicular oxidative damage induced by imidacloprid via modulating the steroidogenesis pathways - Sally Mehanna; Marwa Y. Issa; Neven H. Hassan; Ahmed M. Hussien; Marwa A. Ibrahim; Eman I. Hassanen (Saudi Pharmaceutical Journal, 2022)
The neonicotinoid insecticide imidacloprid has been linked to significant reproductive damage in mammals. Origanum majorana essential oil (OME) is a natural herbal product used in the management of many diseases due to its strong antioxidant effects. The oil was hydrodistilled from O. Majorana and analyzed using GC/MS then its possible protective mechanisms against IMI-induced reprotoxicity in male rats were investigated. 28-adult male Wistar rats were divided into 4 groups as follows: group (1) control group, group (2) OME, group (3) IMI, and group (4) IMI + OME. The treatments were applied daily via oral gavage for 60 days. Remarkable abnormalities in both territorial aggressive and sexual behaviors were observed in IMI-treated rats with a significant elevation of serum FSH and LH as well as altered testicular redox status. Along with inhibition of the testicular expression of StAR and aromatase genes and serum total testosterone in addition to abnormal sperm count, viability, motility, and morphology. Histopathological examination showed severe degeneration and necrosis in both germ cells and Leydig cells with atrophy in most of the seminiferous tubules. Co-administration of OME with IMI notably improved all the above-mentioned studied parameters, and restored rats’ spermatogenesis, sexual behavior, and favorably modulates the levels of both testosterone and gonadotropic hormones via its potent antioxidant effect. These findings support the use of OME as a fertility enhancer and suggest that it could be used to manage pesticide-induced male infertility.